Case report and literature review of late inflammatory reactions to hyaluronic acid filler in a 28-year-old female - Vera, Karim (Aesthetic Medicine, 2024)
Aesthetic procedures with hyaluronic acid (HA) dermal fillers have been rated the second most popular nonsurgical procedure. Although considered as low risked procedures, they can cause significant adverse events. Delayed inflammatory reactions have been a serious problem, characterized by swelling and areas of induration presenting at least 2 weeks after the filler injection. Late-onset nodules had an incidence of less than 1.0 % and may arise from a number of factors, including hypersensitivity, foreign body reaction, injection placement, infection, sterile abscess, or biofilm development. The patient was a 28-year-old female who underwent cheek HA filler and develop delayed onset inflammatory reaction 1.5 months later, presenting purplish nodule on her right cheek. The nodule measured 1 x 1 x 0.5 cm. Ultrasonography and biopsy were not performed due to the patient’s desire to have minimally invasive resolutions to their symptoms as quickly as possible. Strategies recommended for managing delayed onset inflammatory reactions require combination therapy. In this patient, symptoms resolved in 3 weeks after being treated with intralesional hyaluronidase and triamcinolone. To the author knowledge, this is the first case being reported in Indonesia.